a) [1 i 3/7*(-7/10)-4⅖:2⅕]/[3 i 2/9- 4/9] = [10/7(-7/10)-22/5*5/11]/[29/9-4/9]
= [-1-2]/[25/9]
= -3*9/25
= -27/25
= -1 2/25
= -1,08
b)[3 i 5/7*(-⅔)*(-3 i 10/13)+(-6⅓)]/[4 i 2/7+2⅖+(-1 i 3/7)-2 i 6/7] = [26/7*(-⅔)*(-49/13)-19/3]/[30/7+12/5-10/7-20/7] = [28/3-19/3]/[12/5] =
[9/3]/[12/5] =
3*5/12=
15/12=
1 3/12=
1 1/4=
1,25
c) [(4⅙-5⁵/₁₂+7¼)*1⅔]/[-3⅓*4½-3⅓*5½] = [(25/6-65/12+29/4)*5/3]/[-10/3*9/2-10/3*11/2] = [(50/12-65/12+87/12)*5/3]/[-90/6-110/6] =
[72/12*5/3]/[-200/6] =
[6*5/3]/[-200/6] =
[30/3]*[-6/200] =
10*-6/200=
-60/200=
-0,3